Multi-organ involvement secondary to varicella zoster virus, herpes simplex virus and cytomegalovirus in an immunocompromised patient. Issue 3 (31st March 2019) - Jariwala, Ripal; Zeitler, Kristen; Riddle, Nicole D; Sriaroon, Chakrapol
Abstract : The use of immunosuppressing agents can act as a catalyst for viral reactivation, promoting systemic infection with organ involvement. Current literature remains sparse on this topic but does provide individual case reports involving single viruses. We present the case of an immunocompromised patient with skin lesions, pancreatitis, colitis and hepatitis. Work-up revealed varicella zoster virus, which likely put the patient at risk for multi-organ involvement, as well as clinical suspicion of other implicated viruses, specifically herpes simplex virus and cytomegalovirus. A high clinical index of suspicion along with biopsy guidance for viral involvement in immunocompromised patients is crucial for early diagnosis and treatment of these conditions.